Nature of the inflammatory cell infiltrate in duodenitis. Issue 3 (March 1983) - Hasan, M; Hay, F; Sircus, W; Ferguson, A
Abstract : Counts of lamina propria and intraepithelial cells, lymphoid and polymorphonuclear, have been performed on semithin sections of endoscopic biopsies from the duodenum of patients with ulcer-associated duodenitis, with non-specific duodenitis, and from controls. In both types of duodenitis there were significant increases in lamina propria counts of plasma cells, lymphocytes and eosinophils, and in intraepithelial lymphocyte counts, when compared with controls. In control specimens, neutrophil polymorphs were very infrequent but a substantial neutrophil polymorph infiltration of the epithelium and lamina propria was present in both types of duodenitis. In biopsies from areas of duodenitis scanning electron microscopy showed the presence of cells, which are probably neutrophil polymorphs, on the luminal surface of the mucosa. Abnormalities in cell counts were present only in biopsies taken from visually inflamed areas of the duodenal bulb. These values returned to normal after healing of duodenitis with cimetidine. This study highlights the complex nature of the mucosal cellular infiltrate in in duodenitis, particularly the striking increase in polymorphonuclear leucocytes. Histopathological features of ulcer-associated and non-specific duodenitis are identical.